ENUMERATION AND DETERMINATION OF ANTIBIOGRAM OF BACTERIA ISOLATES FROM HAND-DUG WELL WATER IN BOSSO METROPOLIS, NIGERIA - Usman, Aisha; Ekainu, Victor Eche; Adedeji, Abdulameen Saheed; Abdullahi, Hafsah Muhammad; Mustapha, Kaltum Umar; Majin, E. N. (FUDMA JOURNAL OF SCIENCES, 2024)
Regular water supply surveillance is crucial in low-income nations like Nigeria, where households often rely on alternative sources, predisposing preventable water-borne diseases. Therefore, this study determined the occurrence and antibiogram of bacteria in hand-dug well water in Bosso metropolis, Nigeria. Exactly 10 well water samples were collected and processed for bacteria isolation and identification using standard microbiological techniques. The antibiotic sensitivity was determined via Kirby-Bauer disc diffusion techniques. The total viable bacteria count ranged from 0.45×103 cfu/mL to 2.15×104 cfu/mL, while the total coliform bacteria count ranged from 0.27×103 cfu/mL to 8.91×104 cfu/mL. Out of the 18 different bacteria isolated, Pseudomonas species had the highest occurrence (26.9%), and the least (3.9%) was observed for each of Shigella sp., Klebsiella sp., and Staphylococcus aureus. Also, 7 out 26 bacterial isolates isolated were multidrug-resistant. Escherichia coli, Shigella sp., Salmonella sp., Pseudomonas sp., and Klebsiella sp. were susceptible (100%) to ciprofloxacin and ofloxacin, though resistant (100%) to ampicillin and amoxycillin/clavulanate. All the Gram-negative bacteria isolates except Salmonella sp. were susceptible to gentamycin. Similarly, Pseudomonas sp., Proteus sp., and Salmonella sp. exhibited varied resistance to nitrofurantoin (71–100%), cefuroxime (50–100%), and ceftazidime (42.9–100%). Bacillus sp., Enterococcus sp., Staphylococcus sp., and Streptococcus sp. were resistant to cloxicillin and amoxycillin/clavulanate. In addition, Bacillus sp. (100%) and Enterococcus sp. (100%) were resistant to ciprofloxacin while remaining susceptible to ofloxacin and amoxycillin/clavulanate. Our findings highlight the urgent need for enhanced water quality and public health measures in the study areas...